Analisis Kontribusi Pajak Bahan Bakar Kendaraan Bermotor Terhadap Pendapatan Asli Daerah Provinsi Sulawesi Barat - Rusli, Rusli; Sabri, Nurul Ramadhani (LPPM Universitas Muhammadiyah Mamuju, 2022)
The research objectives studied in this study were to determine the contribution of motor vehicle fuel tax to the Regional Original Income of West Sulawesi Province and to find out how big the correlation of the contribution of motor vehicle fuel tax to the Regional Original Income of West Sulawesi Province. This research was conducted at the Regional Finance and Revenue Management Agency of West Sulawesi Province and the Central Statistics Agency of West Sulawesi Province, which were used as secondary data collection sites. The research time lasted for 2 (two) months starting from August to October 2021. The types of data used in this study were qualitative and quantitative. In this study, the data collection method used was secondary and primary data sources. The results of quantitative analysis using a simple linear regression equation formula, from 2016 to 2020 fluctuated where in 2016 the contribution value was 1.81%, in 2017 the contribution value was 1.79%, in 2018 the contribution value was 1.98 %, in 2019 the contribution value was 1.53%, in 2020 the contribution value was 1.94%. The contribution value has a significant influence on the Regional Original Income (PAD) of West Sulawesi Province, this is supported by the results of simple linear regression analysis with a significant value of 0.004 <0.05 and a tcount value of 13.019 > ttable 2.35336, thus the hypothesis is accepted.